The Financial Report Quality, Debt Maturity, and Foreign Ownership on Investment Efficiency Relationship - Wirdanadia, Ananda; Herawaty, Netty; Hernando, Riski (Universitas Trunojoyo Madura, 2024)
This research aims to investigate the effect of financial report quality, debt maturity, and foreign ownership on investment efficiency. This research uses a quantitative method with the population of basic materials sector companies listed on the Indonesia Stock Exchange. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that simultaneously, the quality of financial statements, debt maturity, and foreign ownership do not affect investment efficiency. Partially, debt maturity affects investment efficiency. The quality of financial statements and foreign ownership does not affect investment efficiency. This study provides the main implication, namely the importance of improving the quality of corporate financial management so that investors know essential factors to evaluate investment potential. The financial statement quality ensures accurate information as a basis for making the right investment decisions. Debt to maturity affects liquidity risk and financial stability, and foreign ownership brings better governance practices and access to capital and technology, all of which contribute to improving investment efficiency.